(untitled) (CIPEEX, 2023)
Pre-frailty in the elderly represents an intermediate stage between healthy aging and full frailty. It is crucial to implement early interventions, such as exercise programs, dietary modifications, and psychosocial support, in order to delay or reverse the progression to total frailty. The objective of the study was to verify the prevalence of pre-frailty in elderly residents of a long-term care institution in a municipality in Goiás, as well as their sociodemographic, economic, general health, and functional independence characteristics. A descriptive cross-sectional study was conducted in a long-term care institution for the elderly (ILPI) in the municipality of Rio Verde – Goiás. Elderly residents of the Institution over 60 years old who were classified as pre-frail were included, and those with less than six months of institutionalization were excluded. Data were collected regarding identification, sociodemographic and economic characteristics, general health, and level of frailty (EFE). It was found that 12.0% (n=9) of the evaluated elderly were considered pre-frail, all of whom were male, and most of them had no partner, no level of education, used fewer than 5 medications, and had more than 3 comorbidities. The identification of pre-frail elderly individuals offers a valuable opportunity for the implementation of targeted interventions, such as exercise programs, dietary adjustments, and psychosocial support, in order to delay or even reverse the process of frailty.